2018
DOI: 10.3889/oamjms.2018.333
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Omega 3 and Vitamin E on Palcitaxel-Induced Peripheral Neuropathy

Abstract: BACKGROUND:Paclitaxel-induced peripheral neuropathy is the most important side effect limiting the use of this medication.AIM:This study aimed to compare the effects of omega-3 and vitamin E on the incidence of peripheral neuropathy in patients receiving Taxol.METHODS:In this clinical trial, 63 patients who were a candidate for receiving taxol, were enrolled based on inclusion and exclusion criteria. In group O, patients received 640 mg omega-3 three times a day, and group E, received 300 mg vitamin E two time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Aditionally, we excluded 35 articles that could not extract at least one outcome by screening the full text. Finally, 9 RCTs ( Pace et al, 2003 ; Argyriou et al, 2005 ; Argyriou et al, 2006a ; Argyriou et al, 2006b ; Pace et al, 2010 ; Kottschade et al, 2011 ; Afonseca et al, 2013 ; Salehi and Roayaei, 2015 ; Anoushirvani et al, 2018 ) including 486 patients were enrolled in this study. All articles were published in English, and Table 1 shows the detailed characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aditionally, we excluded 35 articles that could not extract at least one outcome by screening the full text. Finally, 9 RCTs ( Pace et al, 2003 ; Argyriou et al, 2005 ; Argyriou et al, 2006a ; Argyriou et al, 2006b ; Pace et al, 2010 ; Kottschade et al, 2011 ; Afonseca et al, 2013 ; Salehi and Roayaei, 2015 ; Anoushirvani et al, 2018 ) including 486 patients were enrolled in this study. All articles were published in English, and Table 1 shows the detailed characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it was thought that vitamin E supplementation could prevent the development of CIPN or alleviate existing CIPN-related symptoms ( Samuels and Ben-Arye, 2020 ). Additionally, studies have confirmed that vitamin E can be used safely and effectively in CIPN caused by taxanes and cisplatin ( Anoushirvani et al, 2018 ). In summary, the possible mechanisms of vitamin E in CIPN are shown in Figure 1 .…”
Section: Introductionmentioning
confidence: 98%
“…Our search did not reveal dietary patterns to follow in cancer-related pain; however, two clinical trials referred to side-effects of cancer treatment, i.e., aromatase inhibitor-induced musculoskeletal symptoms in breast cancer, which are responsive to vitamin D 2 or D 3 supplementation, respectively [69,70], and another one to neuropathic pain secondary to taxel treatment in breast cancer, with good response to vitamin E or omega 3 supplementation [63]. Vitamin E supplementation 300 mg b.i.d.…”
Section: Discussionmentioning
confidence: 99%
“…Of all pain categories defined most recently by the European Pain Federation [ 1 ], most trials referred to chronic musculoskeletal pain, i.e., low back pain (4 trials) [ 52 , 55 , 64 , 68 ], knee osteoarthritis in obese patients (3 trials) [ 44 , 46 , 74 ], fibromyalgia (7 trials) [ 45 , 47 , 56 , 59 , 61 , 62 , 78 ], neck pain and stiffness (1 trial) [ 79 ], musculoskeletal pain or peripheral neuropathy due to cancer treatment (3 trials) [ 64 , 69 , 70 ], chronic headache or migraine (6 trials) [ 43 , 48 , 49 , 51 , 66 , 67 ], generalized chronic musculoskeletal pain (2 trials) [ 54 , 72 ], diabetic neuropathy [ 50 , 71 ], taxol-induced neuropathic pain [ 63 ], or abdominal pain (10 trials) [ 53 , 57 , 58 , 60 , 65 , 71 , 73 , 75 , 76 , 77 , 80 ]. A synthesis is provided in Table 2 ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation